Investigation of the electrical properties of III-V semiconductor doped with Mn - Al-Ahmadi, Noorah Ahmed (2011)
III-V semiconductors doped with Mn atoms have been studied recently for their potential applications in spintronic devices. These materials are referred to as diluted magnetic semiconductors (DMS) or ferromagnetic semiconductors. The lattice of these materials has Mn atoms (transition metal) and due to their half filled shell carries a spin and also donates carriers, "p-type" in case of Mn doping to the semiconductor lattice. Ferromagnetism is mediated by exchange interactions between localized d electrons and p-type carriers. A high transition temperature (in fact above room temperature) called Curie point, is necessary for these materials to have a practical value. The transition temperature Tc depends on the densities of both Mn impurity and the resultant hole concentration. A low density of defects, a high crystal quality and a high concentration of Mn atoms are desirable to achieve a high Tc.